2021
DOI: 10.1007/s11694-021-01100-8
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric carbon nanotubes based sensor for determination of tryptophan in the milk sample

Abstract: In this research, functionalized carbon nanotubes were employed to modify a glassy carbon electrode (F-MWCNT/GCE). Several techniques including Fourier Transform Infrared Spectroscopy, scanning electron microscopy, and transmission electron microscopy were utilized for characterization of F-MWCNT. The electrochemical activity of the developed electrode was assessed by differential pulse voltammetry, cyclic voltammetry, and electrochemical impedance spectroscopy. The electrochemical results demonstrated that ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 53 publications
1
10
0
1
Order By: Relevance
“…The charge transfer resistance magnitude at the respective electrodes was ascribed to the diameters of the depressed semicircles. As shown, the charge transfer resistance at L-cys@MAPbI3/GCE surface is decreased about 1.7-fold compared to the bare electrode (23.57 kΩ), indicating fast electron transfer on the electrode surface [27]. Results confirmed that the presence of L-cys and MAPbI3 increases the electrode surface's conductivity [28].…”
Section:  / Osupporting
confidence: 54%
“…The charge transfer resistance magnitude at the respective electrodes was ascribed to the diameters of the depressed semicircles. As shown, the charge transfer resistance at L-cys@MAPbI3/GCE surface is decreased about 1.7-fold compared to the bare electrode (23.57 kΩ), indicating fast electron transfer on the electrode surface [27]. Results confirmed that the presence of L-cys and MAPbI3 increases the electrode surface's conductivity [28].…”
Section:  / Osupporting
confidence: 54%
“…The electrochemical active surface area (EASA) was calculated using the Randles-Sevcik equation (Eq. 3) [39,40]. The EASAs value were observed to be 0.062, 0.075, 0.069 and 0.14 cm 2 for GCE, TiO 2 , Ag@TiO 2 /GCE and Ag/TA@TiO 2 /GCE, respectively.…”
Section: Electrochemical Behavior Of Tm At Unmodified and Modified El...mentioning
confidence: 91%
“…Accordingly, measurement methods have been used for many years as a suitable strategy to evaluate the quality of food products [8]. Various measurement methods such as chromatography, spectroscopy, and electrochemical sensors have been proposed to monitor food composition [9][10][11][12][13]. Electrochemical methods have received greater attention than the other techniques [14,15].…”
Section: Introductionmentioning
confidence: 99%